Road accident analysis - Ávila González, Bernald (2014)
The handling and care of a traffic incident better known as "traffic accident” is a process which can be seen in a number of positions and in which the elements involved in the accident are in succession, until it produces result. The problem of the high incidence of mortality from land traffic accidents in the world is a huge concern, this results and responsibilities arising from this type of critical accidents. We cannot let the issue be handled statistically as being so sadly transcendental order in the world. The custom has led us to understand that the problem of traffic accidents is exclusively by public safety, because in them, the police intervene directly, either to prevent, to mediate, or to protect the scene which there are injured or killed. Although many countries are taking important steps to increase road safety, much remains to be done to halt or reverse the increasing trend in the number of fatalities due to traffic accidents.